Local climate action: motives, enabling factors and barriers. Issue 1 (February 2014) - Salon, Deborah; Murphy, Sinnott; Sciara, Gian-Claudia
Background: Despite the relative lack of climate action at the national level in the USA, local climate action is happening. Our focus is on the motivating reasons, stakeholders, and institutional enabler and barrier factors that are directly relevant to making local climate action happen.Results/Methodology: We report here on the results of a two-phase study of local climate action in California (USA): a set of in-depth case studies, and a subsequent web-based survey of all cities and counties in the state.Conclusions: The motives for local climate action often came from within communities and include both tangible local co-benefits of action, as well as the concept that climate action is the 'right thing' to do. Important factors that enable action include strong local champions, supportive residents, and state and national policies and actions. Important barriers to action include lack of local-government staff time and financial resources.